CULTURAL BUREAUCRATIZATION BY IMPLEMENTING CULTURAL- INDEPENDENT VILLAGES ON THE PRIVILEGE OF THE SPECIAL REGION OF YOGYAKARTA - Supardal, Supardal; Widodo Triputro; Tri Nugroho (International Journal of Social Science, 2022)
As a follow-up to the privileges of Yogyakarta in the context of village development through Governor Regulation No.93 of 2020 concerning Cultural-Independent Villages, the government of Yogyakarta states that a village is a model for a plenary village with integrity and innovation that is enlightened and sovereign. The implementation of cultural villages must develop four pillars: the cultural village, the tourist village, the village-preneur, and the prima/women’s role village. To prosper the village community in the context of the privileged culture of Yogyakarta, the four pillars must be developed optimally. For this purpose, cultural-independent villages receive privilege funds between 1 and 1.5 billion rupiahs per year. Consequently, a problem arises: Can the cultural-independent village policy prosper the villagers? Or, is it true that the cultural bureaucratization can realize a plenary village through these four pillars? To examine these problems, researcher(s) collected data through interviews with stakeholders such as the Kundho Kabudayan (Department of Culture) apparatus, cultural village managers or village government, and cultural actors. Furthermore, the data were confirmed with document data so that they were more comprehensive to be analyzed qualitatively and in-depth related to the phenomenon of implementing cultural-independent villages and the dynamics. The results show that, in realizing villages with integrity and innovation that are enlightened and sovereign as an indicator of a cultural-independent village, there was no room to develop following the freedom and independence of the village. However, the villages had been determined by regional apparatus organizations with their standards in the forms of cultural village, tourism village, village-preneur, and prima/women’s role village. Another fact is that there is a cultural bureaucratization by the regional apparatus organizations appointed to the cultural-independent villages so that the villages lose their independence in developing their respective cultures, which are pretty diverse in customs and culture. Likewise, to improve the welfare of the people, a cultural-independent village does not guarantee the economic welfare of the community; in other words, a village with the status of a cultural-independent village may not necessarily have an impact on reducing poverty